2009
DOI: 10.1097/aog.0b013e3181985312
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Pelvic Organ Prolapse at Midlife, Quality of Life, and Risk Factors

Abstract: In our population of women in their 50s, POP symptoms are associated with impaired quality of life, and the number of vaginal deliveries is a risk factor for past or present symptomatic POP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
97
3
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(118 citation statements)
references
References 35 publications
5
97
3
13
Order By: Relevance
“…There is little epidemiological data regarding POP in Japan, despite it being recognized as a disease can be treated in the outpatient or inpatient settings. Moreover, only a few studies have evaluated the distributions of POP according to racial, geographical, and socioeconomic status in the American [7,10,22], British [17], Italian [23], French [24], Turkish [25], Australian [26], and Swedish populations [27]. Therefore, this study aimed to identify the risk factors and prevalence of symptomatic POP among Japanese women.…”
Section: Introductionmentioning
confidence: 99%
“…There is little epidemiological data regarding POP in Japan, despite it being recognized as a disease can be treated in the outpatient or inpatient settings. Moreover, only a few studies have evaluated the distributions of POP according to racial, geographical, and socioeconomic status in the American [7,10,22], British [17], Italian [23], French [24], Turkish [25], Australian [26], and Swedish populations [27]. Therefore, this study aimed to identify the risk factors and prevalence of symptomatic POP among Japanese women.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 This information is relevant to GPs, since the vast majority of pelvic floor symptoms are treated in general practice. The aim of this study was to investigate whether pelvic floor symptoms, pelvic organ prolapse, and other patient characteristics are predictors of sexual inactivity in all women, and of sexual functioning in those women who are sexually active.…”
Section: Introductionmentioning
confidence: 99%
“…[3] The multifactorial pathophysiology may be the cause of associated symptoms such as bladder, bowel, sexual, and even pain symptoms. [4] The symptoms may lead to physical, social, psychological, domestic, and/or sexual limitations in the patient's activities of daily living. [5] A survey done by Muller [6] in the USA found that women with POP experienced compromised bladder and bowel control as most limiting their QOL.…”
mentioning
confidence: 99%